Pathogenicity and virulence of Helicobacter pylori: A paradigm of chronic infection - Marguerite Clyne; Tadhg Ó Cróinín (Virulence)
Infection with Helicobacter pylori is one of the most common infections of mankind. Infection typically occurs in childhood and persists for the lifetime of the host unless eradicated with antimicrobials. The organism colonizes the stomach and causes gastritis. Most infected individuals are asymptomatic, but infection also causes gastric and duodenal ulceration, and gastric cancer. H. pylori possesses an arsenal of virulence factors, including a potent urease enzyme for protection from acid, flagella that mediate motility, an abundance of outer membrane proteins that can mediate attachment, several immunomodulatory proteins, and an ability to adapt to specific conditions in individual human stomachs. The presence of a type 4 secretion system that injects effector molecules into gastric cells and subverts host cell signalling is associated with virulence. In this review we discuss the interplay of H. pylori colonization and virulence factors with host and environmental factors to determine disease outcome in infected individuals.